2007
DOI: 10.1007/s11205-007-9182-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Among Abused Women One Year After Leaving a Violent Partner

Abstract: Intimate partner violence, Follow-up study, Quality of life after separation, SF-36, WHOQOL-BREF,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…These studies used a range of measurement instruments to report on generalized mental health status and functioning. The Medical Outcomes Study 36-item Short Form Health Survey (SF-36) mental health component score was used in five studies [16, 19, 31, 63, 64] and the shorter SF-12 form in two other studies [65, 66]. Other tools used to measure self-reported mental health status were the WHO developed Self-Reporting Questionnaire (SRQ-20) used in three studies [45, 57, 60], the 12-item General Health Questionnaire (GHQ-12) used in three studies [8, 12, 67] and a development of author's own questions [13, 38] or the use of a range of questions extracted from several survey instruments [49].…”
Section: Health Outcomesmentioning
confidence: 99%
“…These studies used a range of measurement instruments to report on generalized mental health status and functioning. The Medical Outcomes Study 36-item Short Form Health Survey (SF-36) mental health component score was used in five studies [16, 19, 31, 63, 64] and the shorter SF-12 form in two other studies [65, 66]. Other tools used to measure self-reported mental health status were the WHO developed Self-Reporting Questionnaire (SRQ-20) used in three studies [45, 57, 60], the 12-item General Health Questionnaire (GHQ-12) used in three studies [8, 12, 67] and a development of author's own questions [13, 38] or the use of a range of questions extracted from several survey instruments [49].…”
Section: Health Outcomesmentioning
confidence: 99%
“…For women who have experienced IPV, continuing abuse and harassment are common post-separation (Alsaker, Moen, & Kristoffersen, 2007;Brownridge, 2006;Mechanic, Weaver, & Resick, 2000) when the risk of both IPV (Johnson & Sacco, 1995) and homicide (Campbell et al, 2003) have been found to increase. In a community sample of Canadian women who had separated from a abusive partners, Davies, Ford-Gilboe, and Hammerton (2008) found that, an average of 20 months post-separation, only 11% of women (N = 309) reported that they had experienced no continuing abuse or harassment.…”
Section: Intrusion Associated With Ongoing Abuse and Harassment From mentioning
confidence: 99%
“…Da mesma maneira, as mulheres que sofreram violência psicológica grave tiveram menos melhora na saúde mental e nas relações sociais. O aumento na qualidade de vida pôde ser verificado no grupo de mulheres que deixaram seus parceiros após sua saída do abrigo (Alsaker et al, 2008).…”
Section: Violência Contra a Mulher E Casas-abrigounclassified